Three zone detection and distance relay co-ordination of power system protection - Cholleti Sriram; Y. Kusumalatha (Institute of Advanced Engineering and Science, 2021)
To secure the transmission lines against power system faults, the distance relays are mostly used. Distance relay has its own Resistance (R)–Reactance (X) characteristics. Co-ordination of different distance relays is necessary for the fast operation of circuit breaker. Various distance relays which are being tripped with respect to circuit breakers which are attached at individual buses faraway from each other. These relays will be operated with respect to the distance between the occurred fault and relay location. In this paper, detection of three zones using relay characteristics, co-ordination of distance relays and circuit breakers are shown with the faults placed at different locations of an IEEE Nine bus system using MATLAB/Simulink GUI environment. A comparison also made between the relays performance and circuit breaker tripping operation with respect to severe faults at different locations on IEEE Nine bus system.